Maternal Dietary Intake of Total Fat, Saturated Fat, and Added Sugar Is Associated with Infant Adiposity and Weight Status at 6 mo of Age. Issue 8 (19th May 2021) - Nagel, Emily M; Jacobs, David; Johnson, Kelsey E; Foster, Laurie; Duncan, Katy; Kharbanda, Elyse O; Gregg, Brigid; Harnack, Lisa; Fields, David A; Demerath, Ellen W
ABSTRACT: Background: Whether current dietary guidelines are appropriate for pregnancy and lactation has not been well studied. Many women of reproductive age are not meeting recommendations for dietary components such as fat, added sugar, and fiber. Objectives: To assess associations between maternal dietary components during pregnancy and lactation and infant growth and adiposity at 6 mo of age. Methods: Mother–infant dyads ( n  = 349) from the prospective, observational Mothers and Infants Linked for Healthy Growth study were included (100% fully breastfed for 1 mo; 75% to 6 mo). Daily intake of fat, fiber, and added sugar was obtained using the National Cancer Institute Diet History Questionnaire II during the third trimester of pregnancy and at 1 and 3 mo postpartum. Furthermore, intakes were categorized as meeting/exceeding 2015–2020 Dietary Guidelines for Americans. Multiple linear regression models adjusted for numerous potential confounders tested relations between dietary components and infant adiposity (via DXA) and growth parameters. Regression coefficients (β) for continuous variables were expressed per SD to allow for comparison of effect sizes. Results: Maternal intake of total fat and saturated fat was positively associated with infant percent body fat (%BF) (β: 0.84 per SD, P  = 0.04; β: 0.96 per SD, P  = 0.01, respectively). Added sugar intake was positively associated with infant weight-for-length z score (β: 0.16 per SD, P  = 0.02), and excessive added sugar intake was positively associated with %BF at 6 mo (β: 0.75 per SD, P  = 0.05). Conclusions: In a predominantly fully breastfeeding cohort of women, maternal intake of fat and added sugar during pregnancy and lactation were associated with small increases in infant adiposity and relative weight at 6 mo. Additional research is needed to determine if these relations persist later in infancy and if such elevations in adiposity are important for long-term obesity risk.